2013
DOI: 10.1016/j.jbtep.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Dutch Intolerance of Uncertainty Scale: Comparison of the full and short version

Abstract: Background and Objectives. The Intolerance of Uncertainty Scale (IUS) was developed for assessing reactions to ambiguous situations, uncertainty, and future events. The IUS has been validated in different languages, but equivocal factor structures, in combination with highly interrelated items and factors, resulted in a redundancy of the items of the English version. In the current study, the psychometric properties of the Dutch version of the IUS were examined, and compared with the shortened 12-item version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 68 publications
8
56
0
3
Order By: Relevance
“…Also, as Sexton and Dugas (2009) had noted, this strategy had excluded other items for consideration at the outset and that might have compromised content validity. Although Sexton and Dugas had demonstrated an excellent fit of the two-factor IUS-27 model to their data, subsequent studies showed less favorable fit indices for this model compared to the two-factor IUS-12 model (Helsen et al, 2013;McEvoy & Mahoney, 2011). As a result, most recent studies examining the construct validity of IUS test scores have relied on the IUS-12 rather than the IUS-27.…”
Section: Factorial Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as Sexton and Dugas (2009) had noted, this strategy had excluded other items for consideration at the outset and that might have compromised content validity. Although Sexton and Dugas had demonstrated an excellent fit of the two-factor IUS-27 model to their data, subsequent studies showed less favorable fit indices for this model compared to the two-factor IUS-12 model (Helsen et al, 2013;McEvoy & Mahoney, 2011). As a result, most recent studies examining the construct validity of IUS test scores have relied on the IUS-12 rather than the IUS-27.…”
Section: Factorial Validitymentioning
confidence: 99%
“…Specifically, prospective IU seems to be more correlated with worry and symptoms of obsessive-compulsive disorder whereas inhibitory IU is more strongly implicated in symptoms of social anxiety, panic disorder, and agoraphobia, posttraumatic stress dis order, and depression (Berenbaum et al, 2008;Fetzner et al, 2013;Helsen et al, 2013;McEvoy & Mahoney, 2011, 2012Sexton & Dugas, 2009). These recent studies documented the differential relations the two aspects of IU have with symptoms of anxiety and mood disorders.…”
Section: Construct Validitymentioning
confidence: 99%
“…Od početka NN se dovodila u vezu sa konceptom nekontrolabilne brige (Helsen, Van den Bussche, Vlaeyen, & Goubert, 2013), za koju se pretpostavlja da igra značajnu (ako ne i centralnu) ulogu u razvoju i održavanju različitih anksioznih poremećaja pre svega GAP-a. Prvi model koji centralno mesto daje NN konstruktu je kognitivni model GAP-a koji su formulisali Dugas i saradnici (Dugas et al, 1998).…”
Section: Uloga Nn U Različitim Modelima Psihopatologijeunclassified
“…Naime, rezultati istraživanja sugerišu postojanje različitog broja latentnih faktora u prostoru od 27 stavki, npr. četvorofaktorsko rešenje (Berenbaum et al, 2008;Buhr & Dugas, 2002;Norton, 2005), dvofaktorsko rešenje (Birrell et al, 2011;Carleton, Norton, & Asmundson, 2007;Helsen et al, 2013;Sexton & Dugas, 2009) itd. U cilju klarifikacije latentne strukture konstrukta NN, Birrell i saradnici (Birrell et al, 2011), u svom preglednom članku, pokušali su da objedine rezultate svih prethodnih studija.…”
Section: Faktorska Struktura Upitničke Operacionalizacije Nnunclassified
See 1 more Smart Citation